BJS Prize 3 PPE-induced systemic hypercapnic-hypoxaemia: translational implications for impaired cognitive-clinical-functional performance. (9th August 2022) - Luton, Oliver; Stacey, Benjamin; Mellor, Katie; Egan, Richard; Bailey, Damian; Lewis, Wyn
Abstract: Background: Personal Protective Equipment (PPE) has been reported to adversely influence pulmonary gas exchange, resulting in systemic hypercapnic-hypoxaemia and cerebral hyperperfusion-induced cephalalgia. This study aimed to determine to what extent these changes impact functional cognition and manual dexterity given their relevance to surgical performance. Method: Thirty-one surgical trainees (20 male, 11 female, aged 29 yr. (29.2 ± 2) participated in a randomised single-blind repeated measures crossover trial, completing one-hour of standardised laparoscopic simulation tasks, on two separate occasions (same day), once in Standard Operating Attire (SOA), and once in full PPE (including FFP3 mask). Global Cerebral Blood Flow (gCBF) was determined using duplex arterial ultrasound. Cognition and manual dexterity were assessed by timed Grooved Pegboard and a novel measure of laparoscopic bead placement. Results: Following one-hour of simulation, PPE (compared with SOA) increased heart rate (93 ± 13 b/min vs. 79 ± 13 b/min, p=0.001), decreased peripheral O2 saturation (96.9% ±1% vs. 97.9% ±1%, p=0.001), increased gCBF (Δ+7 ± 8 mL/min/100g vs. + 1 ± 11 mL/min/100g, p=0.016; reflecting hypercapnic-hypoxic cerebral vasodilatation) and skin temperature increased by 0.6°C (p=0.001). Cephalalgia was reported by 21 (67.7%) participants wearing PPE vs. 13 (41.9%) wearing SOA (p=0.001). Dominant hand pegboard and laparoscopic bead performance were both impaired by PPE: 71.1s (±12) vs. 61.4s (±12), p=0.001; 270.7s (±135) vs. 192.5s (±67), p=0.001 respectively. Conclusion: Collectively, these findings are the first to demonstrate that PPE-induced systemic hypercapnic-hypoxaemia is associated with important impaired cognitive-clinical-functional performance that may have a cerebrovascular basis.